2014
DOI: 10.1016/j.eats.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Graft Preparation Using a Modified Rolling Hitch Technique

Abstract: Anterior cruciate ligament reconstruction using double-looped hamstring autograft is a common procedure in orthopaedic practice. However, during placement of the running, locking stitches at each end of the harvested tendons, the surgeon may face several potential obstacles, including the risk of damaging the tendon, predisposing the surgeon to needle-stick injury, and extended time consumption. We report a modified rolling hitch technique for hamstring graft preparation that is quick, cost-saving, and needlel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…3,4,13 It is clearly not the quickest approach and the desire for a more efficient yet effective option has led to the development of many other stitch configurations. 1,6,8,14 The goals of a simpler and quicker construct are achieved by the SpeedTrap, WhipKnot, and Loop-in-loop constructs. Additionally considering tissue damage during the load to failure testing demonstrates that these three techniques are the least traumatic of those tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,13 It is clearly not the quickest approach and the desire for a more efficient yet effective option has led to the development of many other stitch configurations. 1,6,8,14 The goals of a simpler and quicker construct are achieved by the SpeedTrap, WhipKnot, and Loop-in-loop constructs. Additionally considering tissue damage during the load to failure testing demonstrates that these three techniques are the least traumatic of those tested.…”
Section: Discussionmentioning
confidence: 99%
“…This can be time-consuming, may damage the tendon, and place the surgical personnel at risk for needle sticks. 1 The Krackow stitch 2 has long been a gold standard for this purpose and variations of this stitch have not shown different failure loads. 3 Sakaguchi et al 4 compared different needle based techniques and found that the Krackow stitch was superior to both the whipstitch and the baseball stitch.…”
Section: See Commentary On Page 1170mentioning
confidence: 99%
“…Once achieving a strong fixation strength, early rehabilitation can be allowed before the completion of biologic healing in the graft tunnel. 1 , 2 , 3 , 4 In past decades, various suture techniques have been addressed for tendon graft fixation 1 , 3 , 4 , 5 , 6 , 7 , 8 ; among these techniques, the Krackow suture 6 remains the most popular because it provides superior biomechanical properties. 9 , 10 , 11 …”
mentioning
confidence: 99%
“…In most cases of the single-tendon technique, the ACL graft is formed by a closed tendon loop, which must be secured with sutures at the ends of the graft [6]. The type of loop can vary and different techniques of folding the graft [7][8][9]. Securing its ends with sutures have been described and tested [10][11][12].…”
Section: Introductionmentioning
confidence: 99%